The Liabilities of Enterprises to Adapt to Climate Change in Vietnam - Nguyet, Le Kim; Long, Pham Nguyen Hoang (VNU Journal of Science: Legal Studies; Vol 37 No 1, 2021)
These days many legal documents regarding to climate change in Vietnam have been issued and implemented. Many measures to strengthen and promote the adaptation of enterprises to cope with climate change have been applied, however it remains many shortcomings and inadequacies that have not been addressed, for example, the legal document system in the field is not sufficient and is not concretized in term of adaptation activities to climate change in businesses; tasks of Ministries, govermental organs at all level to respond to climate change are not clear and overlapping, especially the implementation of the current responsibilities of enterprises of which many chanllenges need to be discussed and resolved. Therefore, within the framework of this article, the author will mention about the liabilities of enterprises to adapt to climate change, on that basis, to point out some proposals for amending law in adapting to climate change which are relevant to practical context and for obtaining current sustainable development goals.